Pengaruh Jenis dan Konsentrasi Anti Browning Agent terhadap Warna Tepung Talas Beneng (Xanthosoma undipes K. Koch) - Pardamean Samosir; Merynda Indriyani Syafutri; Nura Malahayati; Desi Aryani; Trubus Airlangga (xxxx-xxxx, 2023)
Samosir P, Syafutri MI, Malahayati N, Aryani D, Airlangga T. 2022. Effect of type and concentration of anti browning agent on color of taro beneng (Xanthosoma undipes K. Koch) flour. In: Herlinda S. et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 991-999. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Taro beneng (Xanthosoma undipes K. Koch) is a local tuber commodity that has the potential to be processed into flour. One of the problems found in flour processing is browning. Enzyme inactivation using anti browning agent is one way to prevent browning. This study aimed to learn the effect of type and concentration of anti browning agent on color of taro beneng flour. This study used a Factorial Completely Randomized Design with two treatment factors, namely type of anti browning agent (sodium metabisulfite and ascorbic acid), and concentration of anti browning agent (500 ppm, 1000 ppm, 1500 ppm, 2000 ppm). The results showed that type of anti browning agent had significant effect on values of lightness, redness, yellowness, browning index, and the degree of whiteness of taro beneng flour, while concentration of the anti browning agent had significant effect on value of redness of beneng taro flour. The interaction between type and concentration of anti browning agent had no significant effect on all parameters. Lightness and degree of whiteness values of taro beneng flour with anti browning agent sodium metabisulfite were higher than taro beneng flour with ascorbic acid.